Influence of Osteopontin Short Hairpin RNA on the Proliferation and Activity of Rat Vascular Smooth Muscle Cells - 叶珊 孙玉梅 别爱桂 周颖 刘佳妮 刘启功 (Journal of Huazhong University of Science and Technology. Medical sciences, 2009)
To investigate the influence of osteopontin （OPN） short hairpin RNA （shRNA） on the proliferation and activity of rat vascular smooth muscle cells （VSMCs）, the expressing vector of shRNA targeting OPN was constructed and transferred into the rat VSMCs. After amplification and purification, pGenesil-1/OPNshRNA1 （PG1）, pGenesil-1/OPNshRNA2 （PG2） and pGenesil-1/OPNshRNAHK （PGH） were transfected into the cultured rat VSMC by LipofectamineTM 2000. Transfected cells were visualized by using an inverted fluorescent microscope. VSMCs transfected by optimal recombined plasmid was selected by culturing in G418 48 h later. Nude cells and cells transfected by PGH were used as control. The expression levels of OPN mRNA and protein were assayed by RT-PCR and Western blotting. The OPN of VSMCs was suppressed by transfection of optimal recombined plasmid, and the changes in cell proliferation, adhesion and motility were evaluated by MTT, adhesion test and transwell chamber test. Levels of type I and Ⅲ collagen were measured with ELISA kit. Our results showed that VSMCs stably transfected by OPN shRNA accounted for over 50% of total cells. OPN mRNA and protein were reduced by 81% and 67% （P〈0.01） by PG1, 73% and 52% （P〈0.01） by PG2, respectively while no change was found in PGH and non-treated VSMCs. PG1 significantly suppressed the proliferation, adhesion, mobility of VSMCs and reduced the amount of type Ⅰ and Ⅲ collagen. It is concluded that recombinant plasmid can be success-fully transfected into VSMCs by LipofectamineTM 2000 and inhibit the expression of OPN. The proliferation, adhesion and mobility of VSMCs can be inhibited by knocking down OPN expression. Moreover, the transferring capability of cells is attenuated, and the secretion of type Ⅰ and Ⅲ collagen is inhibited aftter knocking-down of OPN expression. The study provides experimental evidence for clinical prevention of restenosis after percutaneous coronary intervention （PCI） by RNA interference （RNAi） technology.